2020
DOI: 10.1021/acs.biomac.0c00662
|View full text |Cite|
|
Sign up to set email alerts
|

Microwave-Assisted Ultrafast RAFT Miniemulsion Polymerization of Biobased Terpenoid Acrylates

Abstract: There is a growing preference to move away from traditional petrochemical-based polymers toward biobased alternatives. Here, we report the microwave-assisted RAFT polymerization of several terpenoid acrylates (tetrahydrogeraniol, cyclademol, nopol, and citronellol). These biobased monomers give polymers with a broad range of glass transition temperatures and are excellent candidates to substitute oil-based (meth)acrylates in applications such as coatings and adhesives. First, the process was studied in miniemu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…A number of interesting green material sourcing trends have gathered recent interest, including terpenes, neoligans, amino acids, sugars/carbohydrates, cellulose, silk, and others. Of great interest to us is the terpene limonene, which has been examined for 3D printing directly of the monomer using thiol–ene reactions, modified through thiol–ene chemistry before incorporation into thermoplastic polymers displaying performance/engineering plastic behaviors, and has even been selectively oxidized prior to synthesis of degradable polyesters and polycarbonates. However, polymerization of limonene without modification has been characterized by low yields and oligomeric products. A second terpene of interest is β-myrcene, which possesses a linear structure containing three alkenes and has been utilized as a comonomer with petrochemicals such as styrene as well as with itaconic acid, farnesene, or ocimene. Modification of myrcene commonly focuses on functionalizing with reactive groups such as acrylates or similar derivatives to increase reactivity and better control over the resultant molecular weights. However, a key characteristic of the β-myrcene-containing polymers is the low elastic modulus and high strain at break, with block copolymers particularly demonstrating this behavior …”
Section: Introductionmentioning
confidence: 99%
“…A number of interesting green material sourcing trends have gathered recent interest, including terpenes, neoligans, amino acids, sugars/carbohydrates, cellulose, silk, and others. Of great interest to us is the terpene limonene, which has been examined for 3D printing directly of the monomer using thiol–ene reactions, modified through thiol–ene chemistry before incorporation into thermoplastic polymers displaying performance/engineering plastic behaviors, and has even been selectively oxidized prior to synthesis of degradable polyesters and polycarbonates. However, polymerization of limonene without modification has been characterized by low yields and oligomeric products. A second terpene of interest is β-myrcene, which possesses a linear structure containing three alkenes and has been utilized as a comonomer with petrochemicals such as styrene as well as with itaconic acid, farnesene, or ocimene. Modification of myrcene commonly focuses on functionalizing with reactive groups such as acrylates or similar derivatives to increase reactivity and better control over the resultant molecular weights. However, a key characteristic of the β-myrcene-containing polymers is the low elastic modulus and high strain at break, with block copolymers particularly demonstrating this behavior …”
Section: Introductionmentioning
confidence: 99%
“…Microwave heating has the characteristics of high efficiency and green [ 18 ]. Since Gedye et al [ 19 ] reported that microwave radiation can accelerate the chemical reaction, microwave-assisted organic synthesis has become one of research highlights and has been applied in many fields, such as organic synthesis [ 19 , 20 ], inorganic synthesis [ 21 , 22 ], polymer polymerization [ 23 , 24 ], curing materials [ 25 , 26 , 27 ]. In terms of cured materials, compared with curing in ambient, the curing cycle of carbon fiber epoxy composites cured by the microwave can be shortened by 83% and will not cause new chemical reactions.…”
Section: Introductionmentioning
confidence: 99%
“…Natural products are appealing alternatives to petrochemical sources for polymers, because of their potential to push society toward a more sustainable, circular economy, as well as inherent functionality in many cases. , A popular class of such natural materials is terpenes, of which terpenoids such as linalool are one example. Terpenes have found use in a variety of different polymeric applications, including the development of degradable polyesters and polycarbonates, high T g and performance polymers, and even as initiators or monomers in controlled polymerizations. The successful utilization of terpenes has generally required modifications to terpenoids or terpenes, such as limonene oxide produced from d -limonene or with epoxidized soybean oils. Often this yields polymers with degradable backbones, such as with polyesters and polycarbonates synthesized from limonene oxide; the common alternative is the formation of degradable side chains after functionalization with acrylates. , More recently, this second strategy has been exploited toward 3D printing of natural products, making use of the available functional groups for modification followed typically by free radical crosslinking to produce nondegradable backbones. For example, retinol has been conjugated with poly­(vinyl alcohol) for drug delivery applications, cyclodextrane has been functionalized with acrylate groups for vat photopolymerization, linalool and citronellol were grafted to oligomeric chitosan, , and myrcenol has been projected toward producing functional copolymers and brushes . However, there are other strategies toward photopolymerization 3D printing, such as thiol-ene chemistry, which has been widely utilized for postfabrication functionalization but only sparingly used for additive manufacturing. , …”
Section: Introductionmentioning
confidence: 99%